Dental caries spectrum profile in Brazilian public school children and adolescents - Sofia Rafaela Maito VELASCO; Gustavo Chab PISTELLI; Fernanda Pátaro Marsola RAZERA; Rafael MENEZES-SILVA; Roosevelt Silva BASTOS; Maria Fidela de Lima NAVARRO (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract Dental caries remains a major public health problem, with a higher prevalence among in adolescence. The present study aimed to assess the dental caries spectrum profile in children and adolescents in Brazilian public schools. A cross-sectional study was performed in two public schools in Brazil to examine the permanent teeth of children and adolescents. The dental caries were assessed by applying the Caries Assessment Spectrum and Treatment (CAST) instrument, and the results were distributed as per disease status (healthy/codes 0-2; pre-morbidity/code 3; morbidity/code 4-5; severe morbidity/codes 6-7; mortality/code 8) and by severity as per the CAST-F1 formula (no severity, mild, moderate, and severe). The CAST data were described by age groups (8-9 y, 10-11 y, 12-13 y, 14-15 y, 16-17 y, and 18-19 y). The Kruskal-Wallis test was used to investigate differences in CAST prevalence and severity among the groups (p < 0.05). Total 598 students were enrolled. Most of the subjects were male (53.34%) and belonged to the age group of 12-13 y (34.95%). The variables CAST 0/1 (p = 0.024), CAST (p = 0.024), and CAST-F1 (p = 0.029) showed significant differences among age groups, and the post hoc test showed the differences in these variables as per the age groups of 14-15 y and 16-17 y (CAST 0/1, p = 0.047; CAST, p = 0.047; CAST-F1, p = 0.033). The dental caries spectrum increased from 8 to 19 y with a peak in the prevalence and severity in the middle of adolescence.